Strategi Badan Pendapatan Daerah Dalam Meningkatkan Penerimaan Pajak Bumi Dan Bangunan ( PBB ) Sektor Perkotaan di Kota Pekanbaru - Melia Delvira; Abdul Sadad (Peneliti.net, 2023)
Land and building tax revenues in Pekanbaru City are strived to always increase every year. The percentage of realized land and building tax collection in recent years has been quite effective, but the realization has not reached the target set due to a lack of public awareness in paying land and building tax and the difficulty in submitting SPPT by Bappenda because Bappenda has not optimal taxpayer data. This study aims to analyze the Regional Revenue Agency's Strategy in Increasing Land and Building Tax Revenue in the Urban Sector in Pekanbaru City. One of the strategies carried out by the Pekanbaru City Regional Revenue Agency is optimizing data collection, inspection and collection of regional tax objects in exploring regional revenue potential. Furthermore, improvement and development of human resources, improvement of facilities and infrastructure and finally increasing the performance accountability of the Pekanbaru City government. This study uses Robbins' theory in Yunus (2016) with four indicators, namely: innovation strategy, market differentiation strategy, outreach strategy and cost control strategy. The method used in this study is qualitative, with data collection techniques using interviews, observation, and documentation. Based on the results of the study, it can be concluded that the regional revenue agency's strategy in increasing land and building tax revenues in Pekanbaru City has not run optimally. Keywords : Strategy, Local Own Revenue, Land and Building Tax